Anamnesis peculiarities of BRCA1-associated breast cancer in young women - D. E. Avtomonov; A. A. Parokonnaya; L. N. Lyubchenko; M. I. Nechushkin; D. N. Kravchenko (Опухоли женской репродуктивной системы)
A group of reproductive age patients whose disease is associated with the carriage of BRCA1 gene mutation is of scientific interest. Differences in the molecular pathogenesis between BRCA-associated breast cancer and sporadic counterpart might presuppose anamnesis features of each group as well. We have ascertained that the mean age in young age patients with positive BRCA1 status is 31.8 ± 3.3 years, in 40 % of cases in the family history in the 1st and 2 nd order relatives a breast cancer was identified, in 40 % of cases breast cancer was diagnosed during pregnancy, breast feeding or 1 year post-pregnancy, the disease course in young BRCA1-positive patients is characterized by a 30 % risk of contralateral breast cancer during the first 5 years of observation.